Muscle cramps and contractures: causes and treatment. Issue 1 (15th December 2022) - Dijkstra, Jildou N.; Boon, Eline; Kruijt, Nick; Brusse, Esther; Ramdas, Sithara; Jungbluth, Heinz; van Engelen, Baziel G.M.; Walters, Jon; Voermans, Nicol C.
Abstract : Muscle cramps are painful, sudden, involuntary muscle contractions that are generally self-limiting. They are often part of the spectrum of normal human physiology and can be associated with a wide range of acquired and inherited causes. Cramps are only infrequently due to progressive systemic or neuromuscular diseases. Contractures can mimic cramps and are defined as shortenings of the muscle resulting in an inability of the muscle to relax normally, and are generally myogenic. General practitioners and neurologists frequently encounter patients with muscle cramps but more rarely those with contractures. The main questions for clinicians are: (1) Is this a muscle cramp, a contracture or a mimic? (2) Are the cramps exercise induced, idiopathic or symptomatic? (3) What is/are the presumed cause(s) of symptomatic muscle cramps or contractures? (4) What should be the diagnostic approach? and (5) How should we advise and treat patients with muscle cramps or contractures? We consider these questions and present a practical approach to muscle cramps and contractures, including their causes, pathophysiology and treatment options.